IMPACT OF FILTRATION AND CHLORINATION ON REDUCING CLOGGING IN DRIP EMITTERS - Z. A. Abdullah; A. A. Khalaf (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to reduce the clogging ratio using two waters qualities Sumael (LSI) and Bazalan (LSII). The physical treatment was carried out using complete filtration unit composed of three of filters (Hydrocyclone, Sand, and Disc filters) and application of hypo chloride (Ca (OCl)2 ) 2 ppm as chemical treatment. Generally, physical treatment was more effective than chemical treatment to reduce clogging ratio for Sumael water (LSI). In contrast, for Bazalan water (LSII), the chlorine application was more practical to reduce clogging ratio. The results showed after the period of 320 hr, filtration reduces the clogging ratio for Sumael water (LSI) was 67.77% at clogging ratio 12.51%corresponding to 28.53% at clogging ratio 27.74%for chlorination when the clogging ratio for no treat was 38.82%. As opposed to Bazalan water (LSII), the improvement ratio for chlorination was 14.36% at clogging ratio was 7.56%. In case for filtration was improved to 10.42% when clogging ratio was 8.00% in comparing with no treat clogging ratio was 8.93%.